All Glory Is Fleeting Insights from the Second Lebanon War - Glenn, Russell W. (RAND Corporation, 2012)
The Israeli Defense Forces' efforts to learn from the Second Lebanon War in 2006 and correct recognized deficiencies began immediately after the war's end. Drawing on interviews and written sources, this book reviews identified shortfalls, then offers further thoughts on sources of difficulties and analyzes what lessons the conflict offers the U.S. military.